Method for testing moisture resistance of resin

By testing the resin moisture resistance of carbon fiber reinforced resin-based composite materials, the problem of long-term testing and inaccurate results in the prior art is solved, faster and more accurate test results are achieved, and sample preparation and testing processes are simplified.

CN119827387APending Publication Date: 2025-04-15ZHONGFU SHENYING CARBON FIBER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963835.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the method of evaluating the interface moisture resistance of carbon fiber reinforced resin-based composite materials takes a long time, and the test results are not accurate and intuitive enough.

Method used

A test method for the moisture resistance of resin is provided. By obtaining fiber monofilaments and measuring their diameter, fixing fiber monofilaments on a sheet-shaped carrier, dropping the rubber solution to be tested to form the microspheres to be measured, measuring the diameter of the microspheres, and peeling the microspheres through a clamp to test the breaking force between them and the fiber monofilaments and the diameter of the fiber monofilaments and the microspheres are determined.

Benefits of technology

The test results of this method are more accurate and intuitive, the sample preparation and testing process are simple, and the cycle is short, which can effectively evaluate the moisture resistance of the resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827387A_ABST
    Figure CN119827387A_ABST
Patent Text Reader

Abstract

The invention provides a method for testing the moisture resistance of resin, which comprises the following steps: acquiring a fiber monofilament, and measuring the diameter of the fiber monofilament; fixing the fiber monofilaments on a sheet-shaped carrier provided with holes; dropwise adding a to-be-detected glue solution at the position, corresponding to the hole, of the fiber monofilament, and forming a to-be-detected microsphere on the surface of the fiber monofilament under a preset condition; measuring the diameter of the resin microsphere to be measured; fixing the sheet carrier on a to-be-tested device, stripping the to-be-tested resin microspheres through a clamp, and testing the breaking force between the to-be-tested resin microspheres and the fiber monofilaments; and determining the moisture resistance of the resin according to the diameter of the fiber monofilament, the diameter of the to-be-tested resin microsphere and the breaking force. According to the testing method, by testing the breaking force of the to-be-tested resin microspheres subjected to humidification treatment and the fiber monofilaments and combining the diameters of the fiber monofilaments and the diameters of the to-be-tested resin microspheres, the moisture resistance of the resin can be determined, the testing result of the method is more accurate and visual, the sample preparation and testing process is simple, and the period is short.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite material testing, and in particular to a method for testing the moisture resistance of a resin. Background Art

[0002] Carbon fiber resin composite (CFRP) has the advantages of high specific strength, high specific modulus, strong designability, and good fatigue resistance. It has been widely used in aerospace, vehicles, ships and other fields. However, long-term exposure of CFRP to a humid environment will cause a certain degree of damage to the resin and fiber in it, thereby affecting its interfacial bonding strength and ultimately causing degradation of its mechanical properties. Therefore, the application of CFRP must focus on the impact of environmental humidity on its interface. The general method for evaluating the moisture resistance of the CFRP interface is to control the environmental humidity in an environmental test chamber for dozens of days to several months, and then use a universal testing machine to evaluate its interfacial bonding ability. This is time-consuming and the test results are not accurate and intuitive enough. Summary of the invention

[0003] In order to solve the problems existing in the related art, the present disclosure provides a test method for the moisture resistance of a resin, the test method comprising:

[0004] Obtaining a fiber monofilament and measuring the diameter of the fiber monofilament;

[0005] The fiber monofilament is fixed on a sheet-like carrier with an opening, wherein the extension direction of the fiber monofilament is at a first preset angle to the extension direction of the sheet-like carrier, and the projection of the fiber monofilament on the sheet-like carrier passes through the opening;

[0006] Add the adhesive to be tested at the position corresponding to the opening on the fiber monofilament, and form the microspheres to be tested on the surface of the fiber monofilament under preset conditions; wherein the adhesive to be tested includes the resin to be tested, and the microspheres to be tested include the resin microspheres to be tested;

[0007] Measuring the diameter of the resin microspheres to be tested;

[0008] The sheet carrier is fixed on the device to be tested, and the clamp is adjusted to form a second preset angle with the resin microsphere to be tested in the vertical direction, and the resin microsphere to be tested is peeled off by the clamp to test the breaking force between the resin microsphere to be tested and the fiber monofilament;

[0009] The moisture resistance of the resin is determined according to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force.

[0010] In some embodiments of the present disclosure, the preset condition includes a first preset condition and a second preset condition;

[0011] The method of dripping the test glue solution at the position corresponding to the opening on the fiber monofilament to form the test microspheres on the surface of the fiber monofilament under preset conditions comprises:

[0012] At positions corresponding to the openings on the fiber monofilament, a preset amount of the adhesive solution to be tested is dripped at intervals to form a preset number of microspheres on the surface of the fiber monofilament;

[0013] humidifying the microspheres under a first preset condition;

[0014] The microspheres are solidified under a second preset condition to form the microspheres to be tested.

[0015] In some embodiments of the present disclosure, the adhesive to be tested further includes a curing agent, and the mass ratio of the resin to be tested to the curing agent is 85:1-125:1.

[0016] In some embodiments of the present disclosure, the first preset angle is 0-10 degrees; the second preset angle includes 0-10 degrees.

[0017] In some embodiments of the present disclosure, the diameter of the resin microspheres to be tested is 40-80 mm; and / or,

[0018] The preset number is 10-15.

[0019] In some embodiments of the present disclosure, the first preset condition includes: a preset humidity of 60-90%, a first preset time of 10-25 minutes; and / or,

[0020] The second preset condition includes: a preset temperature of 20-160° C., and a second preset time of 1-48 hours.

[0021] In some embodiments of the present disclosure, the method of peeling off the resin microspheres to be tested by a fixture to test the breaking force between the resin microspheres to be tested and the fiber monofilaments includes:

[0022] The load is applied at a rate of 1-1.5 mm / min, the resin microspheres to be tested are peeled off by the fixture, and the load-displacement curve is tested, and the maximum load is used as the breaking force between the resin microspheres to be tested and the fiber monofilaments.

[0023] In some embodiments of the present disclosure, the method of determining the moisture resistance of the resin according to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force includes:

[0024] According to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force, the interface shear strength between the resin microsphere to be tested and the fiber monofilament is calculated by the following formula, and the moisture resistance of the resin is determined by the interface shear strength:

[0025]

[0026] Among them, σ IFSS is the interface shear strength, in MPa; F max is the breaking force, in cN; D is the diameter of the fiber monofilament, in μm; L is the diameter of the resin microsphere, in μm.

[0027] In some embodiments of the present disclosure, the step of fixing the fiber monofilaments on a sheet-like carrier having openings includes:

[0028] The two ends of the fiber monofilament are fixed on the sheet-like carrier with openings by rosin.

[0029] In some embodiments of the present disclosure, the fiber monofilament is obtained from a carbon fiber tow having a tensile strength of 3500-7000 MPa and a tensile modulus of 200-450 GPa.

[0030] The beneficial effects of the present disclosure include but are not limited to: the test method for the moisture resistance of the resin provided by the present disclosure, the preparation of the test samples of the resin microspheres and the fiber monofilaments to be tested, the breaking force of the resin microspheres and the fiber monofilaments to be tested after humidification treatment, and the combination of the diameter of the fiber monofilament and the diameter of the resin microspheres to be tested, the moisture resistance of the resin can be determined, the test results of this method are more accurate and intuitive, the sample preparation and testing process are simple, and the cycle is short.

[0031] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings incorporated into the specification and constituting a part of the specification illustrate embodiments of the present disclosure and are used together with the description to explain the principles of the embodiments of the present disclosure. In these drawings, similar reference numerals are used to represent similar elements. The drawings described below are some embodiments of the present disclosure, rather than all embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is a flow chart of a method for testing the moisture resistance of a resin according to an exemplary embodiment of the present disclosure;

[0034] Figure 2It is a schematic diagram of a fiber monofilament fixed on a sheet-like carrier with openings according to an exemplary embodiment of the present disclosure. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described in combination with the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure. It should be noted that the embodiments in the present disclosure and the features in the embodiments can be arbitrarily combined with each other without conflict.

[0036] Carbon fiber reinforced resin-based composite materials have the advantages of high specific strength, high specific modulus, strong designability, and good fatigue resistance. They have been widely used in aerospace, vehicle and shipbuilding and other fields. However, long-term exposure of CFRP to a humid environment will cause a certain degree of damage to the resin and fiber therein, thereby affecting its interfacial bonding strength and ultimately causing degradation of its mechanical properties. Therefore, the application of CFRP must focus on the effect of environmental humidity on its interface. The general method for evaluating the moisture resistance of the CFRP interface is to control the environmental humidity in an environmental test chamber for dozens of days to several months, and then use a universal testing machine to evaluate its interfacial bonding ability. This is time-consuming and the test results are not accurate and intuitive enough.

[0037] Based on this, the exemplary embodiment of the present disclosure provides a method for testing the moisture resistance of a resin, such as Figure 1 and Figure 2 As shown, the test method includes:

[0038] S100 , obtaining a fiber monofilament 10 , and measuring a diameter of the fiber monofilament 10 .

[0039] S200 , fixing the fiber monofilament 10 on a sheet carrier 30 provided with an opening 20 , wherein the extension direction of the fiber monofilament 10 and the extension direction of the sheet carrier 30 form a first preset angle, and the projection of the fiber monofilament 10 on the sheet carrier 30 passes through the opening 20 .

[0040] Exemplarily, the sheet carrier 30 may be a rectangular plastic sheet, and the opening 20 may be a circular opening disposed on the sheet carrier 30. The circular opening may be located in the middle of the sheet carrier 30. The projection of the fiber monofilament 10 on the sheet carrier 30 passes through the opening 20, for example, the projection of the fiber monofilament 10 on the sheet carrier 30 passes through the center of the opening 20.

[0041] S300, dripping the adhesive to be tested at the position corresponding to the opening 20 on the fiber monofilament 10, and forming the microspheres to be tested on the surface of the fiber monofilament 10 under preset conditions; wherein the adhesive to be tested includes the resin to be tested, and the microspheres to be tested include the resin microspheres 40 to be tested. The preset conditions include preset humidity conditions, and after dripping the adhesive to be tested on the surface of the fiber monofilament 10, the fiber monofilament 10 attached with the adhesive to be tested is placed under preset humidity conditions for a period of time to humidify the adhesive to be tested. The interface shear strength between the resin microspheres 40 to be tested and the fiber monofilament 10 formed under different preset humidity conditions is different, so the moisture resistance of the resin itself can be determined by testing the interface shear strength between the resin microspheres 40 to be tested and the fiber monofilament 10 after humidification under different preset humidity conditions. For example, the interface shear strength between the resin microspheres 40 to be tested and the fiber monofilaments after being processed under the preset humidity conditions is good, and the moisture resistance of the corresponding resin is good. The interface shear strength between the resin microspheres 40 to be tested and the fiber monofilaments after being processed under the preset humidity conditions is poor, and the moisture resistance of the corresponding resin is poor. For example, the preset humidity conditions can be the real humidity storage conditions of the simulated resin-based composite material. For example, under the real humidity storage conditions, when the storage humidity of the resin-based composite material is 60%, then during the test process, the preset humidity conditions can be set to the test conditions with a humidity of 60%. After the fiber monofilaments 10 attached with the glue to be tested are placed under the test conditions with a humidity of 60% for a period of time, the interface shear strength between the resin microspheres 40 to be tested and the fiber monofilaments 10 formed by the glue to be tested can be tested. The moisture resistance of the resin under the condition of 60% humidity can be further determined. Among them, the placement time can be set according to the real storage time of the resin-based composite material.

[0042] For example, the resin to be tested may be a bisphenol A epoxy resin or a vinyl ester resin.

[0043] For example, 20-30 fiber monofilaments may be selected and 20-30 fiber monofilament test samples may be prepared for repeated testing to improve the accuracy of the test results.

[0044] S400, measuring the diameter of the resin microsphere 40 to be tested.

[0045] S500, fix the sheet carrier 30 on the device to be tested, adjust the clamp 50 to form a second preset angle with the resin microsphere 40 to be tested in the vertical direction, peel off the resin microsphere 40 to be tested by the clamp 50, and test the breaking force between the resin microsphere 40 to be tested and the fiber monofilament 10.

[0046] Exemplarily, the sheet carrier 30 can be fixed on the device to be tested by the upper clamp 70, and the clamp 50 can be adjusted to form a second preset angle with the resin microspheres 40 to be tested in the vertical direction. The resin microspheres 40 to be tested are peeled off by the clamp 50, and the breaking force between the resin microspheres 40 to be tested and the fiber monofilaments 10 is tested, so as to subsequently determine the moisture resistance of the resin based on the breaking force between the resin microspheres 40 to be tested and the fiber monofilaments 10.

[0047] S600, determining the moisture resistance of the resin according to the diameter of the fiber monofilament 10, the diameter of the resin microsphere 40 to be tested, and the breaking force.

[0048] The test method for the moisture resistance of resin provided in this exemplary embodiment prepares test samples of resin microspheres and fiber monofilaments to be tested, and the moisture resistance of the resin can be determined by testing the breaking force of the resin microspheres and fiber monofilaments to be tested formed under preset conditions and combining the diameter of the fiber monofilament and the diameter of the resin microspheres to be tested. The test results of this method are more accurate and intuitive, and the sample preparation and testing process are simple and the cycle is short.

[0049] It should be noted that the interface shear strength between the resin microspheres 40 to be tested and the fiber monofilaments 10 formed by humidification treatment under different preset conditions, that is, different preset humidity conditions, is different. Therefore, the moisture resistance of the resin itself can be determined by testing the interface shear strength between the resin microspheres 40 to be tested and the fiber monofilaments 10 treated under different preset humidity conditions. For example, if the interface shear strength between the resin microspheres 40 to be tested and the fiber monofilaments treated under the preset humidity conditions is good, then the moisture resistance of the corresponding resin is good. If the interface shear strength between the resin microspheres 40 to be tested and the fiber monofilaments treated under the preset humidity conditions is poor, then the moisture resistance of the corresponding resin is poor.

[0050] In an exemplary embodiment provided by the present disclosure, the first preset angle is 0-10 degrees, and the second preset angle includes 0-10 degrees.

[0051] The extending direction of the fiber monofilament 10 and the extending direction of the sheet carrier 30 form a first preset angle, and the first preset angle is 0-10 degrees. For example, the first preset angle can be 0 degrees, that is, Figure 2 As shown in the figure, the extension direction of the fiber monofilament 10 is parallel to the extension direction of the sheet carrier 30. Alternatively, the extension direction of the fiber monofilament 10 and the extension direction of the sheet carrier 30 can also be 3 degrees, 5 degrees or 10 degrees, as long as the fiber monofilament 10 is fixed on the sheet carrier 30 and the partial segments of the fiber monofilament 10 correspond to the positions of the openings 20 of the sheet carrier 30.

[0052] Combination Figure 2As shown, the sheet carrier 30 is fixed on the device to be tested, and the clamp 50 is adjusted to be above the resin microballoon 40 to be tested and to form a second preset angle of 0-10 degrees with the resin microballoon 40 to be tested in the vertical direction, so that the clamp 50 can apply a force of 0-10 degrees to the resin microballoon to be tested in the vertical direction, so as to peel the resin microballoon 40 to be tested and the fiber monofilament 10. For example, the clamp 50 is adjusted to be above the resin microballoon 40 to be tested and to form a second preset angle of 0-10 degrees with the resin microballoon 40 to be tested in the vertical direction, that is, the center of the clamp 50 and the center of the resin microballoon 40 to be tested are in a straight line in the vertical direction, so that the clamp 50 can apply a vertical downward force to the resin microballoon to be tested, so as to peel the resin microballoon 40 to be tested and the fiber monofilament 10, and test the breaking force of the resin microballoon 40 to be tested and the fiber monofilament 10. Alternatively, the angle between the fixture 50 and the resin microsphere 40 to be tested is 3 degrees, 5 degrees or 10 degrees in the vertical direction. It can be understood that, for the peeling of the same resin microsphere 40 to be tested and the fiber monofilament 10, the larger the angle between the fixture 50 and the resin microsphere 40 to be tested in the vertical direction, the greater the breaking force. For the same angle between the fixture 50 and the resin microsphere 40 to be tested in the vertical direction, the greater the breaking force, the greater the corresponding interface shear strength between the resin microsphere 40 to be tested and the fiber monofilament 10, and accordingly, it indicates that the moisture resistance of the resin is better.

[0053] In the exemplary embodiment provided by the present disclosure, the preset conditions include a first preset condition and a second preset condition. Step S300 drips the adhesive to be tested at the position corresponding to the opening 20 on the fiber monofilament 10, and forms the microspheres to be tested on the surface of the fiber monofilament under the preset conditions, including:

[0054] S310, dripping a preset amount of the adhesive solution to be tested at intervals at positions corresponding to the openings on the fiber monofilament 10, so as to form a preset number of microspheres on the surface of the fiber monofilament.

[0055] Exemplarily, a preset amount of the test glue can be dripped at the positions corresponding to the openings on the fiber monofilament 10 at equal or unequal intervals to form a plurality of microspheres to be tested, provide a plurality of test samples, and improve the accuracy of the test.

[0056] S320, humidifying the microspheres under the first preset condition.

[0057] The first preset condition can be a preset humidity condition set according to the humidity condition to be tested by the operator. For example, when testing the humidity resistance of the resin-based composite material under a certain humidity environment, the first preset condition can be set to the same humidity condition as the humidity environment. Alternatively, when the resin-based composite material is tested at the factory, the first preset condition can be set to the extreme humidity condition to test the extreme humidity resistance of the resin.

[0058] S330, curing the microspheres under a second preset condition to form microspheres to be tested.

[0059] After the microspheres are humidified under the first preset conditions, the microspheres are cured under the second preset conditions to solidify the microspheres to form microspheres to be tested, which are then used for subsequent breaking force tests.

[0060] In this embodiment, the glue to be tested is dripped onto the fiber monofilament, and a first preset condition is set according to the environmental conditions required for the test to carry out humidification treatment and then solidification to form a preset number of microspheres to be tested. The moisture resistance of the resin can be determined based on the breaking force of the microspheres to be tested and the fiber monofilament. The test results of this method are more accurate and intuitive, and the sample preparation and testing process are simple and the cycle is short.

[0061] In an exemplary embodiment provided by the present disclosure, the first preset condition includes: a preset humidity of 60-90%, and a first preset time of 10-25 minutes.

[0062] At the positions corresponding to the openings on the fiber monofilament, a preset amount of the adhesive to be tested is dripped at intervals to form a preset number of microspheres on the surface of the fiber monofilament. The sheet carrier fixed with microspheres is placed in a humidity environment with a preset humidity of 60-90% for 10-25 minutes. The resin in the microspheres absorbs water and swells, which can simulate the test of the moisture resistance of the resin in a high humidity environment.

[0063] It should be noted that the preset humidity and the first preset time can be set according to the actual humidity storage conditions and storage time of the simulated resin-based composite material. When selecting resin in the production process of the resin-based composite material, to test the moisture resistance of the resin, the preset humidity can be set to a higher value, such as 60-90%, and the first preset time can be set to 10-25 minutes, so that the moisture resistance of the resin can be quickly tested.

[0064] In the exemplary embodiment provided in the present disclosure, the second preset condition includes: a preset temperature of 20-160° C., and a second preset time of 1-48 hours.

[0065] After the microspheres are humidified, the sheet carrier with the microspheres fixed thereon can be placed in a vacuum drying oven with a preset temperature of 20-160° C. and dried for 1-48 hours to allow the microspheres to solidify on the surface of the fiber monofilaments to form microspheres to be tested, which can be used for subsequent breaking force tests.

[0066] In the exemplary embodiment provided in the present disclosure, the diameter of the resin microspheres to be tested is 40-80 mm, and the preset number is 10-15.

[0067] In order to ensure the accuracy of the breaking force test and reduce errors, the diameter of the resin microspheres to be tested formed by dripping the glue to be tested on the surface of the fiber monofilament should not be too different, and the diameter should be kept as uniform as possible. In this embodiment, the diameter of the resin microspheres to be tested is limited to 40-80 mm, which can avoid the resin microspheres to be tested being too small, which is not conducive to the clamping and peeling of the clamp, and can also avoid the resin microspheres to be tested being too large, which increases the consolidation area between the resin microspheres to be tested and the fiber monofilament, affecting the accuracy of the breaking force test results and interfering with the test of the resin moisture resistance.

[0068] At the positions corresponding to the openings on the fiber monofilament, 10-15 drops of the test glue solution can be dripped at equal or unequal intervals to form 10-15 test microspheres. This can provide multiple test samples through one sample preparation, thereby improving the accuracy of the test.

[0069] In the exemplary embodiment provided in the present disclosure, the adhesive to be tested also includes a curing agent, and the mass ratio of the resin to be tested to the curing agent is 85:1-125:1.

[0070] The resin to be tested for moisture resistance is added with a curing agent to prepare a test glue solution. The mass ratio of the resin to be tested and the curing agent is limited to 85:1-125:1, which can ensure that the resin can be cured on the surface of the fiber monofilament and condensed into balls, so that the moisture resistance of the resin can be determined by testing the breaking force of the resin microspheres and the fiber monofilament.

[0071] In the exemplary embodiments provided in the present disclosure, the adhesive solution to be tested may further include other additives or solvents, and the components and contents of the adhesive solution to be tested may be set according to the actual resin formula to be tested.

[0072] In the exemplary embodiment provided by the present disclosure, the resin microspheres to be tested are peeled off by a fixture to test the breaking force between the resin microspheres to be tested and the fiber monofilaments, including:

[0073] The load is applied at a rate of 1-1.5 mm / min, the resin microspheres to be tested are peeled off through a fixture, and the load-displacement curve is tested, and the maximum load is taken as the breaking force between the resin microspheres to be tested and the fiber monofilaments.

[0074] refer to Figure 2As shown, the fixture 50 is adjusted to an angle above the resin microsphere 40 to be tested and parallel to the resin microsphere 40 to be tested in the vertical direction, so that the fixture 50 can apply a vertical downward force to the resin microsphere to be tested, and the fixture 50 applies a load at a rate of 1-1.5mm / min to peel off the resin microsphere 40 to be tested, so as to avoid the resin microsphere to be tested being peeled off too quickly due to the excessive rate and unable to accurately detect the real-time load. Among them, the fixture 50 can be connected to a mechanical sensor to test the load of the fixture 50 in real time, and the mechanical sensor can be connected to a computing control device, which can form a load-displacement curve based on the load measured in real time by the mechanical sensor, and use the maximum load as the breaking force between the resin microsphere to be tested and the fiber monofilament, and stop applying the load when the load drops to 70% of the maximum load.

[0075] The moisture resistance of the resin can be determined later based on the breaking force of the resin microspheres and fiber monofilaments to be tested.

[0076] In the exemplary embodiment provided by the present disclosure, the moisture resistance of the resin is determined according to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force, including:

[0077] According to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force, the interface shear strength between the resin microsphere to be tested and the fiber monofilament is calculated by the following formula. The moisture resistance of the resin is determined by the interface shear strength:

[0078]

[0079] Among them, σ IFSS is the interface shear strength, in MPa; F max is the breaking force, in cN; D is the diameter of the fiber monofilament, in μm; L is the diameter of the resin microsphere, in μm.

[0080] In this embodiment, according to the diameter D of the fiber monofilament, the diameter L of the resin microsphere to be tested, and the breaking force F max , calculate the interface shear strength between the resin microspheres to be tested and the fiber monofilaments, which is the interface shear strength between the resin and the fiber monofilaments remaining after the resin is humidified, and can reflect the moisture resistance of the resin. A high interface shear strength indicates that the resin has strong moisture resistance, and a low interface shear strength indicates that the resin has weak moisture resistance. The method provided in this embodiment is used to determine the moisture resistance of the resin, and the test results are intuitive and accurate, which can provide guidance for the preparation and storage of resin-based composite materials.

[0081] Exemplarily, the number of valid data for determining the interface shear strength each time is not less than 10, and the coefficient of variation is not higher than 15%.

[0082] In the exemplary embodiments provided in the present disclosure, Figure 2As shown, the fiber monofilament 10 is fixed on a sheet-like carrier 30 having an opening 20, comprising:

[0083] Both ends of the fiber monofilament 10 are fixed to the sheet-like carrier 30 having the opening 20 by means of the rosin 60 .

[0084] The rosin 60 has a fast curing speed. At the moment when the fiber monofilament 10 is bonded to the sheet carrier 30 through the rosin 60, the rosin 60 can be quickly cured to fix the fiber monofilament 10 on the sheet carrier 30, thereby reducing the curing time and preventing the fiber monofilament 10 from falling off or shifting due to its own soft characteristics during the fixing process.

[0085] In the exemplary embodiments provided in the present disclosure, the fiber monofilaments are obtained from carbon fiber tows having a tensile strength of 3500-7000 MPa and a tensile modulus of 200-450 GPa.

[0086] In order to avoid the fiber monofilaments from breaking or falling off during the test of the breaking force due to the insufficient strength of the fiber monofilaments themselves, in this embodiment, the fiber monofilaments are obtained from carbon fiber tows with a tensile strength of 3500-7000MPa and a tensile modulus of 200-450GPa, which can ensure the strength of the fiber monofilaments during the test and prevent the insufficient strength of the fiber monofilaments from affecting the test of the moisture resistance of the resin. For example, the length of the carbon fiber tow can be 5-10cm, or it can be cut according to the size of the sheet carrier.

[0087] In order to more clearly explain the technical solution of the present disclosure, a specific example of a method for testing the moisture resistance of a resin provided by an exemplary embodiment of the present disclosure is given below.

[0088] Example 1

[0089] Fiber monofilament diameter test: Select 12K carbon fiber tow (tensile strength ≥ 6600MPa, tensile elastic modulus 330-350GPa), and use GB / T 29762-2013 method B to test the carbon fiber monofilament diameter, recorded as D.

[0090] Test sample preparation: Cut the carbon fiber tow to 10cm, pick out a single carbon fiber monofilament under the sample preparation lamp and fix it on a plastic sheet, and fix the two ends with rosin. In an environment with a temperature of 22-25℃ and a humidity of 35-40%, prepare the glue to be tested, according to the mass ratio of AG80 epoxy resin and curing agent of 1:2. After the glue to be tested is mixed evenly, use the sample preparation needle to dip the glue to be tested and drop it on the surface of the carbon fiber monofilament, and add 10 drops of glue on the surface of each carbon fiber monofilament.

[0091] Humidification treatment: After the adhesive to be tested is added, the carbon fiber monofilament is transferred to an environmental test box, the ambient humidity is set to 70%, and the humidification treatment is performed for 10 minutes.

[0092] Carbon fiber monofilament curing: The sample after humidification treatment was cured according to the AG80 epoxy resin curing process: curing at 80°C for 1.5 hours, 120°C for 2 hours, and 150°C for 3 hours to form the resin microspheres to be tested.

[0093] Breaking force microsphere test: After curing, use a microsphere debonding tester to test the interfacial bonding strength between the carbon fiber monofilament and the resin microsphere to be tested. Place the plastic sheet on the sample stage of the microsphere debonding tester, use the upper clamp to fix the top of the plastic sheet, use a 1cN clamp under the plastic sheet to provide pre-tensioning force, and adjust the clamp to keep the carbon fiber monofilament in a vertical position. Select the resin microsphere to be tested with a diameter between 40-80um under the electronic magnifying glass, measure the diameter of the resin microsphere to be tested, and record it as L. Adjust the clamp position to above the resin microsphere to be tested, adjust the clamp opening to be slightly smaller than the diameter of the resin microsphere to be tested, set the loading rate of the microsphere debonding tester to 1mm / min, test the load-displacement curve, and take the maximum load as the breaking force F of the resin microsphere to be tested. max , combined with the diameter L of the resin microsphere to be tested and the diameter D of the carbon fiber monofilament, the interface shear strength σ is calculated IFSS , According to the data distribution, select the ten data closest to the average value, calculate the average value and CV value, and control the CV value to be less than 15%. The test data are shown in Table 1.

[0094] Example 2

[0095] The difference between this embodiment and embodiment 1 is that the humidification treatment time is extended. In the humidification treatment step, the carbon fiber monofilament after the glue to be tested is transferred to the environmental test box, the environmental humidity is set to 70%, and the high humidity treatment is carried out for 25 minutes. According to the data distribution, the ten data closest to the average value are selected, the average value and CV value are calculated, and the CV value is controlled to be less than 15%. The test data is shown in Table 1.

[0096] Example 3

[0097] The difference between this embodiment and embodiment 1 is that the humidity of the humidification treatment is reduced. In the humidification treatment step, the carbon fiber monofilament after the glue to be tested is added is transferred to the environmental test box, the environmental humidity is set to 60%, and the high humidity treatment is carried out for 10 minutes. According to the data distribution, the ten data closest to the average value are selected, the average value and CV value are calculated, and the CV value is controlled to be less than 15%. The test data is shown in Table 1.

[0098] Example 4

[0099] The difference between this embodiment and embodiment 1 is that the humidity of the humidification treatment is increased. In the humidification treatment step, the carbon fiber monofilament after the glue to be tested is transferred to the environmental test box, the environmental humidity is set to 90%, and the high humidity treatment is carried out for 10 minutes. According to the data distribution, the ten data closest to the average value are selected, the average value and CV value are calculated, and the CV value is controlled to be less than 15%. The test data is shown in Table 1.

[0100] Example 5

[0101] The difference between this embodiment and embodiment 1 is that the composition and curing process of the glue to be tested are changed. In the test sample preparation step, E44 epoxy resin is selected to prepare the glue to be tested. In an environment with a temperature of 22-25°C and a humidity of 35-40%, the glue to be tested is prepared according to a mass ratio of E44 epoxy resin: triethylenetetramine: acetone of 10:1:2.5. After the environmental test chamber treatment, it is cured at 130°C for 70 minutes. According to the data distribution, the ten data closest to the average value are selected, the average value and CV value are calculated, and the CV value is controlled to be less than 15%. The test data is shown in Table 1.

[0102] Example 6

[0103] The difference between this embodiment and embodiment 1 is that the composition and curing process of the adhesive to be tested are changed. In the test sample preparation step, VEH-90 vinyl ester resin is selected to prepare the adhesive to be tested. In an environment with a temperature of 22-25°C and a humidity of 35-40%, the adhesive to be tested is prepared according to a mass ratio of VEH-90 vinyl ester resin: curing agent of 100:1. After the environmental test chamber treatment, it is cured for 48 hours in an environment with a temperature of 22-25°C and a humidity of 35-40%. According to the data distribution, the ten data closest to the average value are selected, the average value and CV value are calculated, and the CV value is controlled to be less than 15%. The test data is shown in Table 1.

[0104] Example 7

[0105] The difference between this embodiment and embodiment 1 is that the test rate is increased. In the breaking force microsphere test step, the loading rate of the microsphere debonding tester is set to 1.5 mm / min, and the load-displacement curve is tested. According to the data distribution, the ten data closest to the average value are selected, the average value and CV value are calculated, and the CV value is controlled to be less than 15%. The test data is shown in Table 1.

[0106] Table 1

[0107] Example <![CDATA[Interfacial shear strength σ IFSS (MPa)]]> Cv(%) Example 1 45.5 12.3 Example 2 38.6 14.8 Example 3 47.6 10.2 Example 4 37.8 9.8 Example 5 16.8 10.9 Example 6 63 14.2 Example 7 54.1 12.6

[0108] It can be seen from Table 1 that the test method for the moisture resistance of resin provided by the exemplary embodiment of the present disclosure has a low coefficient of variation Cv of the test result, and the test result is accurate and has high credibility.

[0109] The contents described above may be implemented individually or in combination in various ways, and these variations are all within the protection scope of the present disclosure.

[0110] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0111] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present disclosure.

Claims

1. A method for testing the moisture resistance of a resin, characterized in that: The test method includes: Obtaining a fiber monofilament and measuring the diameter of the fiber monofilament; The fiber monofilament is fixed on a sheet-like carrier with an opening, wherein the extension direction of the fiber monofilament is at a first preset angle to the extension direction of the sheet-like carrier, and the projection of the fiber monofilament on the sheet-like carrier passes through the opening; Add the adhesive to be tested at the position corresponding to the opening on the fiber monofilament, and form the microspheres to be tested on the surface of the fiber monofilament under preset conditions; wherein the adhesive to be tested includes the resin to be tested, and the microspheres to be tested include the resin microspheres to be tested; Measuring the diameter of the resin microspheres to be tested; The sheet carrier is fixed on the device to be tested, and the clamp is adjusted to form a second preset angle with the resin microsphere to be tested in the vertical direction, and the resin microsphere to be tested is peeled off by the clamp to test the breaking force between the resin microsphere to be tested and the fiber monofilament; The moisture resistance of the resin is determined according to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force.

2. The method for testing the moisture resistance of a resin according to claim 1, characterized in that: The preset condition includes a first preset condition and a second preset condition; The method of dripping the test glue solution at the position corresponding to the opening on the fiber monofilament to form the test microspheres on the surface of the fiber monofilament under preset conditions comprises: At positions corresponding to the openings on the fiber monofilament, a preset amount of the adhesive solution to be tested is dripped at intervals to form a preset number of microspheres on the surface of the fiber monofilament; humidifying the microspheres under a first preset condition; The microspheres are solidified under a second preset condition to form the microspheres to be tested.

3. The method for testing the moisture resistance of a resin according to claim 1 or 2, characterized in that: The test glue solution also includes a curing agent, and the mass ratio of the test resin to the curing agent is 85:1-125:

1.

4. The method for testing the moisture resistance of a resin according to claim 1 or 2, characterized in that: The first preset angle is 0-10 degrees; the second preset angle includes 0-10 degrees.

5. The method for testing the moisture resistance of resin according to claim 2, characterized in that: The diameter of the resin microspheres to be tested is 40-80 mm; and / or, The preset number is 10-15.

6. The method for testing the moisture resistance of resin according to claim 2, characterized in that: The first preset condition includes: a preset humidity of 60-90%, a first preset time of 10-25 minutes; and / or, The second preset condition includes: a preset temperature of 20-160° C., and a second preset time of 1-48 hours.

7. The method for testing the moisture resistance of resin according to claim 1, characterized in that: The method of peeling off the resin microspheres to be tested by a fixture and testing the breaking force between the resin microspheres to be tested and the fiber monofilaments comprises: The load is applied at a rate of 1-1.5 mm / min, the resin microspheres to be tested are peeled off by the fixture, and the load-displacement curve is tested, and the maximum load is used as the breaking force between the resin microspheres to be tested and the fiber monofilaments.

8. The method for testing the moisture resistance of resin according to claim 7, characterized in that: The method of determining the moisture resistance of the resin according to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force comprises: According to the diameter of the fiber monofilament, the diameter of the resin microsphere to be tested, and the breaking force, the interface shear strength between the resin microsphere to be tested and the fiber monofilament is calculated by the following formula, and the moisture resistance of the resin is determined by the interface shear strength: Among them, σ IFSS is the interface shear strength, in MPa; F max is the breaking force, in cN; D is the diameter of the fiber monofilament, in μm; L is the diameter of the resin microsphere, in μm.

9. The method for testing the moisture resistance of resin according to claim 1, characterized in that: The method of fixing the fiber monofilaments on a sheet-like carrier provided with openings comprises: The two ends of the fiber monofilament are fixed on the sheet-like carrier with openings by rosin.

10. The method for testing the moisture resistance of a resin according to claim 1 or 2, characterized in that: The fiber monofilament is obtained from a carbon fiber tow having a tensile strength of 3500-7000 MPa and a tensile modulus of 200-450 GPa.